Sharia Business: Halal Tourism-Based Community Empowerment - Setiyani , Wiwik; Nurhairunnisa (International Journal of Halal Research, 2023)
This paper aims to capture the problems and the dynamics of halal tourism in Trowulan, Mojokerto, Indonesia. The research uses the Participatory Action Research (PAR) method by relying on the involvement and participation of community members as a key instrument to turn plans and solutions into actual policies. Milton Friedman’s positive economic theory becomes an analytical instrument by integrating the data, logic, and methodology to analyze halal tourism community empowerment in Trowulan. The results are: [1], the implementation of religious tourism empowerment is conducted through structural planning, scenarios, and methodologies that include data and benefits, both economically and spiritually. [2], Community involvement reduces the risk of low resistance and policy-makers can determine optimum policies for religious tourism development in Trowulan. [3], Community empowerment through socialization, mentoring, and training conducted by the local government (and the management team) can increase public concern and interest.